MULTICULTURAL HERITAGES IN A CITY AS PRODUCTIVE TOURISM PLACES - PRATIWI, WIWIK D. (ASEAN Journal on Hospitality and Tourism, 2011)
A city can be a place for productive tourism places. Bandung, for example, has become a tourists' city and especially benefited from weekend visitors from Jakarta. Visitors in the city are offered attractions for leisure and consumption. The city's attractions are dominated by heritages: from pattern of street layout to the existence of a distinctive architecture, to the variety of activities to create the city itself as a visitors' experience. These conditions need a deliberate attempt to create the city as multicultural places of consumption for both retail and tourism as part of urban cultural management. This paper examines the creation of the city as a tourism destination. It is argued that changes to the process of capital accumulation in many cities have led to the commodification of place at a local level. Part of this process has been the creation of heritage as a tangible asset and this is linked to changing patterns of consumer retail activity. This paper argued that tourism should not be conceptualized as a distinct activity but rather as a form of consumption in the context of both local and global changes.